Infusoabdomen with abdominal compartment in extremely low birth weight neonates - Armin-Johannes Michel; Johannes Brandner; Sebastian Cotofana; Mircia Ardelean; Roman Metzger (Elsevier, 2016)
Central venous catheters (CVCs) are frequently used in neonatal care. The rate of complications upon CVC use is high and the spectrum ranges from catheter tip dislocation to cardiac tamponade and death. Here we present an explanation model to the phenomenon of paravasate into human anatomical cavities based on two illustrative cases: Extremely low birth weight twins suffering from abdominal compartment syndromes due to different pathologies - one with a trans-peritoneal and one with intra-abdominal effusion. In both siblings the peripherally introduced central catheter (PICC) perforated the vessel without clinical signs of bleeding and contributed to abdominal and thoracal complications. Case I (23 + 5 gestational week; 770 g; female) showed clinical signs of an abdominal compartment syndrome without respective intestinal pathology upon open surgical procedure with ileostomy. Radiographic contrast examination showed retroperitoneal leakage when administered through the catheter. Replacement into the subclavian vein led to cardio-respiratory misbalance due to severe pleural effusion. Re-replacement finally led to clinical restitution after 60 days of intensive care. Case II (23 + 5 gestational week; 690 g; female) showed clinical signs of an abdominal compartment syndrome, too. Radiographic contrast examination showed leakage from the PICC into the abdomen. Replacement of the PICC and invasive care led to improvement after 3 days. The 2 cases reveal that the displacement of a PICC can occur without direct clinical signs of hemodynamic imbalance i.e. bleeding or hematoma. Displacement of the catheter tip from intra-vascular, retro-peritoneal position can cause abdominal compartment syndromes either via trans-peritoneal migration of fluids or after perforation of the peritoneum via intra-abdominal administration of given infusion. Both options caused life threatening complications. Watchfulness and intensive surgical and non-surgical care are indicated to handle these severe complications.